Evaluation of Respiratory Symptoms among Workers in an Automobile Manufacturing Factory, Iran - Bahram HARATI; Seyed Jamaleddin SHAHTAHERI; Ali KARIMI; Kamal AZAM; Alireza AHMADI; Maryam AFZALI RAD; Ali HARATI (Tehran University of Medical Sciences, 2018)
Background: This study estimated the prevalence of respiratory symptoms and disorders among workers exposed to exposure to volatile organic compound (VOCs) in an automobile manufacturing factory in Tehran, Iran in 2016. Methods: Subjects of this case-control research were included 80 samples including 40 workers exposed to different level of BTEX as well as 40 unexposed individuals were considered as control group. Methods 1501 and 7602 presented by the National Institute of Occupational Safety and Health (NIOSH) were used for the sampling and analysis of compounds in the air. Gas Chromatography-Flame Ionization Detector (GC-FID) was used for analysis of compounds of interest. Six silica samples were collected during the campaign. Silica analyses were performed by using visible absorption spectrophotometry system. Lung functions were evaluated for 80 workers (40 exposed, 40 nonexposed) using spirometry system. Results: The average amount of total dust and free silica measured in factory were 7.3±1.04 mg.m-3 and 0.017±0.02 mg.m-3 respectively. Average benzene, toluene, ethyl-benzene and xylene exposure levels in exposed subject's median were 0.775±0.12, 1.2±2.08, 45.8±8.5, and 42.5±23.9 ppm respectively. Statistical tests showed significant difference between pulmonary function tests (except PEF) of exposed and non-exposed individuals before and after employment (P<0.05). Workers exposed to VOCs presented lower levels of FVC, VC, and PEF than the control group except FEV1/FVC%, FEV1, FEF2575 and FEV1/VC%. Conclusion: Decline in lung volumes and respiratory symptoms, significant difference associated with the exposure to dust or gas, duration of exposure, and smoking habit. Therefore, lung function tests should be performed before and after the employment to identify sensitive workers candidates.